Small-molecule modulators of serine protease inhibitor proteins (serpins). Issue 2 (February 2021) - Kellici, Tahsin F.; Pilka, Ewa S.; Bodkin, Michael J.
Highlights: Targeting serpins with drug-like molecules remains a challenge in drug discovery. Compounds targeting HSP47, antitrypsin, antithrombin, PAI-1 and neuroserpin are analysed. The compounds either target the physiological role of serpins or their polymerisation. The mode of action of these compounds is analysed, if known. Virtual screening and other in silico techniques have been successful in identifying new chemical matter. Abstract : Serine protease inhibitors (serpins) are a large family of proteins that regulate and control crucial physiological processes, such as inflammation, coagulation, thrombosis and thrombolysis, and immune responses. The extraordinary impact that these proteins have on numerous crucial pathways makes them an attractive target for drug discovery. In this review, we discuss recent advances in research on small-molecule modulators of serpins, examine their mode of action, analyse the structural data from crystallised protein–ligand complexes, and highlight the potential obstacles and possible therapeutic perspectives. The application of in silico methods for rational drug discovery is also summarised. In addition, we stress the need for continued research in this field. Teaser: The discovery of drug-like chemical matter targeting proteins with multiple conformational states, such as serpins, remains a challenge in drug discovery. This review examines recent advances in serpin therapeutic design.